The role behind the scenes of Tregs and Th17s in Hashimoto’s thyroiditis: Toward a pivotal role of FOXP3 and BACH2 - Mazzieri, Alessio; Montanucci, Pia; Basta, Giuseppe; Calafiore, Riccardo (Frontiers in Immunology, 2022)
In Hashimoto's thyroiditis (HT), the genetic bases play a central role in determining development of the disease. In particular, the most frequent genes involved in the onset of HT are the Human Leukocyte Antigen (HLA). However, there are other genes and transcription factors in the autoimmune background of HT, both isolated and as part of autoimmune polyendocrine syndromes (APS). Recently more interest is being fueled toward BACH2 (BTB Domain and CNC Homolog 2), that promotes Tregs (T regulators lymphocytes) differentiation and enhances Treg-mediated immunity. The synergistic interaction between environmental agents and the aforementioned genes leads to the onset of autoimmunity and ultimately to damage of the thyroid gland. In this scenario, the role of Th17 (T helper-17 lymphocytes) and Treg cells is still less defined as compared to action of Th1 cells (T helper-1 lymphocytes) and cytotoxic lymphocytes (CD8 + T lymphocytes). Evidences show that an imbalance of Th17/Treg ratio represents a prognostic factor with respect to the gland damage. Moreover, the deficient ability of Treg to inhibit the proliferation of T cells against the self can break the immune balance. In light of these considerations, the use of genetic panels and the progress of immunotherapy could allow for better targeting treatment and preventive interventions in subjects with potential or early stage of HT.